2017
DOI: 10.18632/oncotarget.18413
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EIF4F complex in non-small cell lung cancer cells

Abstract: Non-small cell lung cancer (NSCLC) accounts for about 85–90% of lung cancer cases, which represents the leading cause of cancer-related death in the world. The majority of lung cancer patients doesn't respond well to conventional chemo-/radio-therapeutic regimens and have a poor prognosis. The recent introduction of targeted therapy and immunotherapy gives new hopes to NSCLC patients, but their outcome/prognosis is far from satisfactory. The translation initiation EIF4F complex has been shown to play important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Non-small cell lung cancer (NSCLC) accounts for approximately 85-90% of lung cancers, which are the most common fatal malignancy and leading cause of cancer mortality worldwide [1,2]. It is reported that the median overall survival (OS) with platinum-based chemotherapy is approximately 7.5-28.2 months among advanced NSCLC patients, and the median progression-free survival (PFS) is approximately 2.1-6.9 months [3].…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for approximately 85-90% of lung cancers, which are the most common fatal malignancy and leading cause of cancer mortality worldwide [1,2]. It is reported that the median overall survival (OS) with platinum-based chemotherapy is approximately 7.5-28.2 months among advanced NSCLC patients, and the median progression-free survival (PFS) is approximately 2.1-6.9 months [3].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the most common cancer and the leading cause of cancer death worldwide, with approximately 2.1 million new cases (11.6% of the total new cases) and 1.76 million deaths (18.4% of the total deaths) [1,2]. Of the two major types of lung cancer, non-small cell lung cancer (NSCLC) accounts for about 85% to 90% of all lung cancers, which typically has a slower rate and double time than small cell lung cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that eIF4A promotes the translation of mRNAs with long and structured 5′UTR features [ 20 , 21 ]. To confirm that IL-24 translationally down-regulates expression of long and structured 5′UTR mRNAs, HeLa cells were co-transfected with Renilla (control) and Firefly FF) luciferase reporters harboring structured 5′UTRs or unstructured 5′UTRs.…”
Section: Resultsmentioning
confidence: 99%